2020
DOI: 10.3390/ijms21093299
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mesenchymal Stem Cells in Counteracting Oxidative Stress—Related Neurodegeneration

Abstract: Neurodegenerative diseases include a variety of pathologies such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, and so forth, which share many common characteristics such as oxidative stress, glycation, abnormal protein deposition, inflammation, and progressive neuronal loss. The last century has witnessed significant research to identify mechanisms and risk factors contributing to the complex etiopathogenesis of neurodegenerative diseases, such as genetic, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 194 publications
(199 reference statements)
3
25
0
1
Order By: Relevance
“…7a-b). Studies showed that abnormal changes in intracellular ROS and Ca 2+ levels were correlated with various neurodegenerative diseases [47][48][49][50]. In the present study, the ROS and intracellular Ca 2+ levels were signi cantly higher in SCA3/MJD-NCs compared with Ctr1-NCs, while obviously decreased in the corrected SCA3/MJD-NCs ( Fig.…”
Section: Reversal Of Mitochondrial Dysfunction and Oxidative Stress Asupporting
confidence: 61%
See 2 more Smart Citations
“…7a-b). Studies showed that abnormal changes in intracellular ROS and Ca 2+ levels were correlated with various neurodegenerative diseases [47][48][49][50]. In the present study, the ROS and intracellular Ca 2+ levels were signi cantly higher in SCA3/MJD-NCs compared with Ctr1-NCs, while obviously decreased in the corrected SCA3/MJD-NCs ( Fig.…”
Section: Reversal Of Mitochondrial Dysfunction and Oxidative Stress Asupporting
confidence: 61%
“…The phenotypic abnormalities occurred in SCA3/MJD stem cell models were different from previous studies, which lay a valuable cellular models for pathological mechanism research. Altogether, these results may indicate that mutant ataxin3 could enhance Ca 2+ release from endoplasmic reticulum storages, then causing Ca 2+ overload and eventually cell death, accompanied by mitochondrial permeability, oxidative stress, cytoskeletal tissue destruction, and/or calpain activation [47][48][49][50].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Considering the above information, it is crucial to develop treatments that can reduce α-syn aggregation and impede PD progression. Interestingly, cell-based therapies with mesenchymal stem cells (MSCs) and their secretomes have been shown to cross the BBB, which explains their use in the treatment of NDDs [ 16 ]. MSCs are self-renewing and multipotent progenitor cells, and their beneficial effects against NDDs were mainly due to the factors they secrete, rather than cellular engraftment in models of PD [ 17 , 18 ], demonstrating the neuroprotective ability of MSC-conditioned medium (MSCs-CM).…”
Section: Introductionmentioning
confidence: 99%
“…SCs are obtained from the patient's own bone marrow and intravenously administered into the spinal cord. One year later, 30% epilepsy patients had a complete remission (without seizures), and 50% epilepsy patients who had not previously responded to the medication began to respond well [18][19][20].…”
Section: Characteristics Types and Therapy Of Stem Cellsmentioning
confidence: 99%